Expand (x-y)^3

We know that (x-y)3 can be written as

(x-y)(x-y)(x-y)

We know that (x-y)(x-y) can be multiplied and written as

x2-xy -yx +y2 (x-y)

= x2-2xy +y2 (x-y)

= x3-2x2y +xy2-yx2+2xy2-y3

= x3-3x2y +3xy2-y3

Answer

(x-y)3=x3-3x2y +3xy2-y3

Was this answer helpful?

  
   

4 (7)

Upvote (7)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question